A multi-regional energy transport and structure model for China's electricity system. (15th October 2018) - Zhang, Yaru; Ma, Tieju; Guo, Fei
Abstract: The imbalance between the distribution of coal resources and electricity demand makes the transport of energy a significant challenge for China's electricity system. Moreover, with China's air pollution control policies, more clean energy resources will be used to generate electricity, which will change regional power generation structures and influence the energy transport among regions. In this paper, a multi-regional model is developed to optimize the long-term generation and transmission structure of China's electricity system by minimizing the accumulative system cost and considering regional resource endowments and air pollution control polices in four key areas. Results indicate that 1) the share of power generation from clean energy will increase from 24% in 2015 to 62% in 2050, 2) the structure of power generation in each region will be influenced by local water resource availability, and the total CO2 emission will be reduced by around 16% in 2030 owing to the air pollution control policies, and 3) by 2050, coal will be mainly transported from the North to the Central, the South, the East and the Northeast, while the electricity will be transmitted to the Central, the South and the East from the Northwest, the North, the Southwest and the Central. Highlights: A multi-regional optimization model of China's electricity system is developed. The share of clean energy generation will increase from 24% in 2015 to 62% in 2050. Resource endowment and environmental policy will affect regional energy structure. The energy transport between regions are mapped from 2020 to 2050.